1982
DOI: 10.1073/pnas.79.17.5142
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of simian virus 40 Hpa II site affects late, but not early, viral gene expression.

Abstract: DNA methylation has been correlated with reduced gene expression in a number of studies, although evidence for a causal link between the two events has been lacking. Because microinjection of simian virus 40 (SV40) DNA into the nucleus of Xenopwu laevis oocytes results in the synthesis of both early and late viral gene products, it was possible to test whether a specific methylation event can affect gene expression. The single SV40 Hpa H site at 0.72 SV40 map units was specifically methylated with Hpa H methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…Equally convincing is another series of experiments in which genes were methylated in vitro before transfer into eukaryotic cells. For example, methylation of all CpG dinucleotides in the Moloney retrovirus genome virtually abolishes its expression , and in simian vims 40 (SV40) methylation of a single Hpall (CCGG) site inhibits late gene transcription when tested in the frog oocytes (Fradin et al 1982; see also Vardimon et al 1982). However, it is noteworthy that methylation affects SV40 early promoter function neither in frog oocytes nor in mammalian cells (Fradin et al 1982;Graessmann et al 1983).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Equally convincing is another series of experiments in which genes were methylated in vitro before transfer into eukaryotic cells. For example, methylation of all CpG dinucleotides in the Moloney retrovirus genome virtually abolishes its expression , and in simian vims 40 (SV40) methylation of a single Hpall (CCGG) site inhibits late gene transcription when tested in the frog oocytes (Fradin et al 1982; see also Vardimon et al 1982). However, it is noteworthy that methylation affects SV40 early promoter function neither in frog oocytes nor in mammalian cells (Fradin et al 1982;Graessmann et al 1983).…”
mentioning
confidence: 99%
“…For example, methylation of all CpG dinucleotides in the Moloney retrovirus genome virtually abolishes its expression , and in simian vims 40 (SV40) methylation of a single Hpall (CCGG) site inhibits late gene transcription when tested in the frog oocytes (Fradin et al 1982; see also Vardimon et al 1982). However, it is noteworthy that methylation affects SV40 early promoter function neither in frog oocytes nor in mammalian cells (Fradin et al 1982;Graessmann et al 1983). In the 7-globin gene, the methylation state of the promoter region is most critical for gene expression, whereas extensive methylation of the coding sequence is tolerated (Busslinger et al 1983;Murray and Grosveld 1987).…”
mentioning
confidence: 99%
“…Although experiments with some genes show that DNA methylation has powerful effects at selective individual sites in the 5' region (2)(3)(4), other studies indicate that methylation may work over the entire gene domain (5), probably by interfering with the formation of a normal active chromosomal conformation (6).…”
mentioning
confidence: 99%
“…5-10; refs. 5 and 6 are reviews), and several studies in which cloned eukaryotic genes were methylated in vitro have demonstrated a direct inhibitory effect on transcription (11)(12)(13)(14). In addition, a variety of studies in cell culture systems have shown that 5-azacytidine, a cytotoxic pyrimidine analog that inhibits DNA methylation, can induce cellular differentiation (15) and either directly activate (16) or allow activation of specific genes (17).…”
mentioning
confidence: 99%